2020
DOI: 10.1016/j.cortex.2019.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor conflicts alter metacognitive and action monitoring

Abstract: Bodily self-consciousness is defined as a set of prereflective representations of integrated bodily signals giving rise to self-identification, self-location and first-person perspective. While bodily selfconsciousness is known to modulate perception, little is known about its influence on higher-level cognitive processes. Here, we manipulated bodily self-consciousness by applying sensorimotor conflicts while participants performed a perceptual task followed by confidence judgments. Results showed that sensori… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…In a factorial design, we also tested for the effect of continuous report paired to stimulus presentation on confidence judgements. Over conditions with and without first-order 2AFC responses (both R+ and R-), we found a consistent increase in confidence following continuous report (CR+ vs. CR-) , as well as the existence of sub-threshold motor activity (Gajdos et al, 2019), differences in movement parameters (Faivre et al, 2019) or voluntary control (Charles et al, 2019). Our study adds a novel kind of manipulation, namely the occurrence of motor responses, to the list of experimental manipulations that affect confidence but not first-order accuracy.…”
Section: Effect Of Continuous Report On Confidence Ratingsmentioning
confidence: 53%
See 1 more Smart Citation
“…In a factorial design, we also tested for the effect of continuous report paired to stimulus presentation on confidence judgements. Over conditions with and without first-order 2AFC responses (both R+ and R-), we found a consistent increase in confidence following continuous report (CR+ vs. CR-) , as well as the existence of sub-threshold motor activity (Gajdos et al, 2019), differences in movement parameters (Faivre et al, 2019) or voluntary control (Charles et al, 2019). Our study adds a novel kind of manipulation, namely the occurrence of motor responses, to the list of experimental manipulations that affect confidence but not first-order accuracy.…”
Section: Effect Of Continuous Report On Confidence Ratingsmentioning
confidence: 53%
“…Beyond behaviour alone, Gajdos et al (2019) showed that confidence increases in the presence of sub-threshold motor activity prior to first-order responses. Plus, we recently showed that alpha-desynchronization prior to first-order response (an electrophysiological signature of motor preparation) correlates with confidence over different perceptual tasks (Faivre et al, 2017), that metacognitive performance for decisions that are committed with a keypress is better than that to equivalent decisions that are observed (Pereira et al, 2018), and that sensorimotor conflicts alter confidence (Faivre et al, 2019). Finally, transcranial magnetic stimulation (TMS) directed at the premotor cortex involved in the first-order response was found to affect confidence ratings, suggesting a causal role of action-related signals for confidence (Fleming et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…More generally, our theory suggests that failures of the ego-centric system would render the perceptual system more susceptible to false percepts and hallucinations. Interestingly, recent work suggests that sensorimotor conflicts induced by a robotic system decrease the capacity to adapt confidence to task performance (metacognitive failure), increase intentional binding (potentially due to an enhanced JoA) (Faivre et al, 2020) and generate a feeling of presence (Blanke et al, 2014).…”
Section: Explanatory Power and Novel Predictionsmentioning
confidence: 99%
“…Participants' pokes were replicated by the back robot, thus applying corresponding touches on participants' backs. The touches were mediated by the robot either in synchronous (without delay) or asynchronous (with 500 milliseconds delay) fashion, creating different degrees of sensorimotor conflict between the upper limb movement and somatosensory feedback on the back (Blanke et al, 2014;Faivre et al, 2020;Salomon et al, 2020).…”
Section: Robotic Systemmentioning
confidence: 99%
“…induces an alteration of BSC characterized by differences in self-location (Blanke et al, 2014) and in selfmonitoring (Faivre et al, 2020). Importantly, these and related stimulations also induce the feeling that another person is in the room (Blanke et al, 2014;Salomon et al, 2020), a loss of self-agency (Sato & Yasuda, 2005;Tsakiris, Haggard, Franck, Mainy, & Sirigu, 2005), and somatic passivity (i.e.…”
Section: Introductionmentioning
confidence: 99%